STUDI KELAYAKAN BISNIS PADA PRODUK PIVYSWEET SITUBONDO - Khomariyah, Sit Nur; Mufida, Nurul Lailatul; Tarqiyah, Urwatut; Nurcahyo, Subro Wahyu; Aziz, Moh. Abdul; Sya'diya, Yuli Halimatus (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Pivysweet is one of the MSMEs that operates in the food industry in the form of mochi. Pivysweet is located in East Lugundang District, RT01/RW06, Situbondo, East Java. This mochi has various flavors, namely strawberry cream cheese, strawberry chocolate, silverqueen chocolate, matcha, creamy mango. The type of research we conducted was qualitative research that used phenomenology as a method and data collection technique based on observation, interviews with the owner of Pivysweet Situbondo and documentation.